Zirconium-Loaded Mesostructured Silica Nanoparticles Adsorbent for removal of Hexavalent Chromium from Aqueous solution - S., Triwahyono; Jalil, A. A.; Salamun, N.; Majid, Z. A.; Mamat, C. R.; Basar, N.; Setiabudi, H. D.; Prasetyoko, D.; Hartanto, D.; Mukti, R. R. (2018)
Chromium is one of the heavy metals present in effluents produced from the aerospace, electroplating, leather, mining, dyeing, fertilizer, and photography industries [1]. In the aqueous phase, chromium mostly exists in two oxidation states, namely, trivalent chromium (Cr3+, Cr(OH)2+, or Cr(OH)2+, etc.) and hexavalent chromium (HCrO4-, CrO42-, or Cr2O72-, etc.). Most of the hexavalent compounds are considered to be more hazardous due to their carcinogenic properties, which can cause severe health problems in humans. Therefore, it is essential to reduce the Cr(VI) content of wastewater to below the tolerance limit before it is discharged into the environment [2]. Several research groups have developed technologies to reduce the Cr(VI) content from aqueous media, such as adsorption, electrochemical precipitation, ion exchange, and reverse osmosis techniques [2-5]. Among these technologies, adsorption has been regarded as an easy and efficient method to remove Cr(VI), owing to its relatively low cost and simplicity of design and operation. The conventional adsorbents for adsorption of organic and inorganic metal compounds have been studied widely, and include activated carbon, zeolite, natural clay, and biomaterials [6-9]. However, the inherent drawbacks associated with most of these adsorbents leads to relatively low adsorption capacity and selectivity, mechanical and thermal instability, or the need for a longer equilibrium time, even though the adsorbents may be cheap, to some extent, in practice. Therefore, the development of an adsorbent with a good Cr(VI) removal ability would be desirable.